Dento-facial aesthetics in the eyes of adolescent patients during the Covid-19 pandemic. - Cherecheş Jessica Olivia; Moca Abel Emanuel; Vaida Luminiţa Ligia; Bembea Marius ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2021)
Introduction: Dental malocclusions are considered a major issue in adolescence, and are often the main reason for which patients go to the dentist. Adolescents' option to start an orthodontic treatment is questioned in the light of the restrictions imposed in the context of the Covid-19 pandemic.